Training for a Future Teacher. Introduction to Inclusion for Primary School Students Through Literary Works - Гордійчук, Оксана Євгенівна (My University, 2022)
Relevance of the topic is defined by the professional standards for the specialty: a primary school teacher for general secondary educational institutions, that require development of “inclusive competence” directed towards forming “a skill for pedagogical support of persons with special educational needs” in primary school students.1 One of the tools for development of this competence is the use of literary works on inclusion facilitating the forming of children’s consciousness and influencing the perception of children with disabilities by school students. We concur and think that literary works on inclusion will help primary school students to understand, accept and respect every person no matter of his/her special features and professional training of the specialist for introducing children to the concept is necessary.
Keywords: Training; Future Teacher; Primary School